Distribution Manner of Compaction Circular Cylinders in Through-Active-Mask Electrochemical Machining. (February 2015) - Li, Hansong; Wang, Guoqian; Zheng, Xin; Zeng, Yongbin
Electrochemical machining is widely used in the processing of difficult-to-machine metal materials. And through-mask electrochemical machining is a very important technology in the processing array structure of difficult-to-cut metal materials. Traditional through-mask electrochemical machining always uses a photoresist as the mask. The production process of a mask is complicated, and the mask cannot be reused. In this paper, through-active-mask electrochemical machining to process array structure in difficult-to-machine metal materials was investigated. Compared with traditional electrochemical machining masks, a copper-clad laminate is used to make the mask by mechanical machining in through-active-mask electrochemical machining. Also, the mask does not stick together with the workpiece but covers the workpiece by mechanical compaction, so the mask can be reused. In order to ensure the mask is in close contact with the workpiece, we need to arrange many compaction circular cylinders within the flow channel. The influences on electrolyte flow of compaction circular cylinders were investigated. The distribution of the compaction circular cylinders affects the electrolyte flow state, thereby affecting the processing. By analyzing the electrolyte flow state for the different distributions of compaction circular cylinders, one can find the best distribution of compaction circular cylinders for the required processing.